The origin of fast‐charging lithium iron phosphate for batteries - Mohammed Hadouchi; Toshinari Koketsu; Zhiwei Hu; Jiwei Ma (Battery Energy, 2022)
Abstract Since the report of electrochemical activity of LiFePO4 from Goodenough's group in 1997, it has attracted considerable attention as cathode material of choice for lithium‐ion batteries. It shows excellent performance such as the high‐rate capability, long cyclability, and improved safety. Furthermore, the raw materials cost of LiFePO4 are lower and abundant compared with conventional Li‐ion battery oxides compounds. The lithium extraction from LiFePO4 operates as biphase mechanism accompanied by a relatively large volume change of ∼6.8%, even though, nanosized LiFePO4 shows exceptionally high‐rate capability during cycling. In the aim to explain this remarkable feature, recent reports using cutting‐edge techniques, such as in situ high‐resolution synchrotron X‐ray diffraction, explained that the origin of the observed high‐rate performance in nanosized LiFePO4 is the absence of phase separation during battery operation at high current densities. In this review, the importance of understanding lithium insertion mechanisms towards explaining the significantly fast‐charging performance of LiFePO4 electrode is highlighted. In particular, phase separation mechanisms, are unclear and deserve considerable attention. Several proposed models for Li diffusion and phase separation in LiFePO4 are summarized. In addition, the crystallographic aspects, defect structures of LiFePO4 are also reviewed. Finally, the status of development of other olivine‐type LiMPO4 (M = Co, Mn, and Ni) are summarized.